Exploring The Cause And Consequences Of Repeated Fire Outbreaks In Monrovia, Liberia - Forkpah, Eric (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa Tanah Datar Sumatera Barat, 2024)
Fire outbreaks pose significant threats to communities worldwide, causing loss of life, property damage, and environmental degradation. This paper explores the causes and consequences of repeated fire outbreaks in Monrovia, Liberia, drawing insights from global incidents such as the Grenfell Tower fire in London and the Camp Fire in Paradise, California. By analyzing specific incidents and case studies, the study highlights the multifaceted nature of fire outbreaks, including factors such as human error, electrical faults, and environmental vulnerabilities. It underscores the importance of proactive measures, such as regular inspections, adherence to safety protocols, and strengthening regulations, in mitigating fire risks and enhancing fire safety. Additionally, the paper emphasizes the critical role of community involvement, accessible emergency services, and education in enhancing resilience and mitigating the impact of fire emergencies. The findings underscore the necessity for integrated approaches involving stakeholders at various levels to address fire risks and enhance community resilience.